Music, spirituality and dementia: Exploring joint working between pastoral care professionals and music therapists to improve person-centred care for people with dementia (Innovative Practice). (January 2021) - Connolly, Lyndsey; Moss, Hilary
This paper presents innovative practice in the area of interdisciplinary collaboration between pastoral care and music therapy professionals to meet the spiritual needs of people with dementia in a hospital environment. Our qualitative research identified the following themes to guide future endeavours in this area: Music has the capacity to facilitate spiritual expression; music therapy contributes to validating the individuality of the person with dementia; collaborative work between music therapy and pastoral care is worthy of further exploration. This study is one of few to address the potential for combining pastoral care and music therapy in the care of people with dementia.